Traumatic Coronary Artery Dissection as A Potential Cause of Acute Myocardial Infraction in Motorcycle Accident - Tondas, Alexander Edo; Tandri, Fredy; Zulkarnain, Edrian (Jurnal Kardiologi Indonesia, 2022)
Background: Chest pain in blunt chest trauma can be caused by various intrathoracic injuries. Pneumothorax, hemothorax, and rib fractures are commonly seen in the emergency department. Although cardiac involvement is very rare, the probability should not be excluded. Case Illustration: A-31-years-old male who complained of chest pain and diaphoresis was brought to the emergency department after a high-speed motorcycle collision. Chest X-ray revealed no abnormality but a 12-lead Electrocardiogram (ECG) demonstrated ST-segment elevation in lead I, AvL, V2-6, and atrial fibrillation. Because of the unusual presentation, the decision was to proceed with percutaneous coronary intervention (PCI). Coronary Angiography detected a thrombus at proximal LAD and spiral dissection at mid LAD (TIMI 2 Flow). After the procedure, he was transferred to the High Care Unit. Conclusion: Following blunt chest trauma, chest pain in the setting of a vehicle collision can be caused by dissection of the coronary artery. Prompt cardiac workup (ECG, cardiac enzyme, and echocardiography) must be done in a highly suspected patient.